2016
DOI: 10.1259/bjr.20150409
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of radiation techniques in the treatment of mediastinal lymphoma: from 3D conformal radiotherapy (3DCRT) to intensity-modulated RT (IMRT) using helical tomotherapy (HT): a single-centre experience and review of the literature

Abstract: Improvement of radiation techniques for HL and NHL appears to improve the tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Our results are in line with a SEER-based study in patients with stages 1 and/or 2 DLBCL, which found that CVM rates were higher in patients treated without RT. 25 A possible explanation for these observations is that, according to clinical practice guidelines, 26 patients treated with RT receive 27 However, these results need to be interpreted with caution because our study follow-up period was shorter than other published data that found an association between radiation and increased CVM (3 years vs 19 years, respectively), 28 and we did not have information about site, dose, or field of RT treatment.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Our results are in line with a SEER-based study in patients with stages 1 and/or 2 DLBCL, which found that CVM rates were higher in patients treated without RT. 25 A possible explanation for these observations is that, according to clinical practice guidelines, 26 patients treated with RT receive 27 However, these results need to be interpreted with caution because our study follow-up period was shorter than other published data that found an association between radiation and increased CVM (3 years vs 19 years, respectively), 28 and we did not have information about site, dose, or field of RT treatment.…”
Section: Discussionmentioning
confidence: 73%
“…A possible explanation for these observations is that, according to clinical practice guidelines, patients treated with RT receive fewer chemotherapy cycles, which translates into a lower risk of chemotherapy‐related cardiotoxicity. Also, improvements in RT techniques have decreased the amount of incidental radiation to the heart, thereby reducing associated complications . However, these results need to be interpreted with caution because our study follow‐up period was shorter than other published data that found an association between radiation and increased CVM (3 years vs 19 years, respectively), and we did not have information about site, dose, or field of RT treatment.…”
Section: Discussionmentioning
confidence: 83%
“…It has high imaging accuracy and automatically corrects positioning errors before radiotherapy, which makes the target area conformability and dose distribution more reasonable. TOMO integrates three-dimensional conformal radiation therapy, intensity-modulated radiation therapy, image-guided radiation therapy, dose-guided radiation therapy, adaptive radiation therapy, and other radiotherapy technologies in one, could be clinically used for a variety of tumors throughout the body, especially for frequently occurring tumors and tumors adjacent to important organs and tissues, which improves the accuracy of the target area while reducing the occurrence of complications (11,12). All patients in this study used TOMO to treat lung metastases, and this has a certain research value.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent studies, RP is becoming less and less frequent, mainly due to technological advances in RT and the increasing knowledge of its etiology ( 26 , 27 ). However, it still remains as a complication that may interfere with quality of life in cancer patients.…”
Section: Discussionmentioning
confidence: 99%